PEMANFAATAN TAMAN BACAAN MASYARAKAT SEBAGAI PUSAT PEMBELAJARAN OLEH MASYARAKAT DI NAGARI KANDANG BARU KABUPATEN SIJUNJUNG - Prasetia, Yogi (Education For All, 2022)
The background of this research is that the kandang baru village reading park has been used well by the community, the cause is the large collection of books in TBM, the existence of complete supporting facilities, thus the purpose of this study is (1) to describe the use of TBM as a learning center by children school age (2) describes the use of TBM as a learning center by RT's mother (3) describes the use of TBM as a learning center by farmer groups. This research is a quantitative descriptive study with a population of 51 people and a sample of 25 people. The data collection technique in this study was a questionnaire with percentage data analysis. The results of the study show that the description of the use of TBM which includes (1) TBM has been used well by school children as a learning center (2) TBM has been used well by RT as a learning center (3) TBM has been used well by members of farmer groups as a learning center. learning center.